2018
DOI: 10.4103/jlp.jlp_9_17
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of bone marrow involvement in non Hodgkin’s lymphoma classified according to WHO classification: Report of a developing country Pakistan

Abstract: BACKGROUND:Limited information is available from developing countries in patients of non-Hodgkin's lymphoma (NHL). Hence, we reviewed the demographical profile along with bone marrow infiltration pattern in patients with NHL presented at Liaquat National Hospital and Medical College.MATERIALS AND METHODS:In this descriptive study, adult patients with NHL were enrolled from January 2011 to December 2015.RESULTS:One hundred and Eighty-four histopathologically confirmed cases of NHL were identified. There were 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 10 publications
3
27
2
Order By: Relevance
“…Possibly shorter life expectancy and relatively younger population in developing countries might be one explanation of this disparity 17 . Moreover, B symptoms were observed among 96% of our patients which was different from study conducted by Sultan et al, where B symptoms were common among 80.4% patients 18 . The difference might be due to the fact that they included only NHLs in their study while we studied both Hodgkin and NHLs.…”
Section: Discussioncontrasting
confidence: 99%
“…Possibly shorter life expectancy and relatively younger population in developing countries might be one explanation of this disparity 17 . Moreover, B symptoms were observed among 96% of our patients which was different from study conducted by Sultan et al, where B symptoms were common among 80.4% patients 18 . The difference might be due to the fact that they included only NHLs in their study while we studied both Hodgkin and NHLs.…”
Section: Discussioncontrasting
confidence: 99%
“…Kumar S et al [11] in a study on 49 cases of Non Hodgkin lymphoma found that the overall incidence of marrow involvement by Non Hodgkin lymphoma was 55.1%. Sultan S et al [12] found the frequency of bone marrow inltration in Non Hodgkin lymphoma patients to be 31.5% (58/187) . Kittivorapart J et al [13] found the incidence of bone marrow involvement in cases of Non Hodgkin lymphoma to be 23.8% which is on the lower side when compared to our study.…”
Section: Resultsmentioning
confidence: 99%
“…Maximum number of cases were seen in the age group of 51 to 60 years (mean age 52.1 years and median age 59.5 years). Maximum number of patients (12) with bone marrow involvement also belonged to the age group of 51 to 60 years (median 60 years). Male preponderance was seen and constituted 66.7% cases and females constituted 33.3% with male to female ratio of 2:1.…”
Section: Resultsmentioning
confidence: 99%
“…Another reason is that CT is not effective in diagnosis lymphoma being not reliable in the detection of bone marrow disease, which, if present, by definition indicates stage IV disease 4 . 18 F-FDG PET/CT has an impact on the assessment of both newly diagnosed, prognosed and previously treated patients with lymphoma and also alters the initial clinical staging of this disease 5,6 . Incidence of marrow disease varies with histological subtype of lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…Bone marrow biopsy is fundamental in identifying marrow involvement for therapy purpose 7 . Marrow diseases can be diagnosed with 18 F-FDG PET/CT scan and the visual interpretation of marrow FDG uptake throughout whole-body. PET scans can efficiently determine marrow disease status in a high proportion of lymphoma patients.…”
Section: Introductionmentioning
confidence: 99%